Sex differences in out-of-hospital cardiac arrest interventions within the province of British Columbia, Canada. (1st March 2020) - Awad, Emad; Christenson, Jim; Grunau, Brian; Tallon, John; Humphries, Karin
Abstract: Introduction: Out-of-hospital cardiac arrest (OHCA) is common among females and males alike; however, previous studies reported differences in outcomes between sexes in different regions. To investigate possible explanations for this disparity, we examined sex differences in resuscitation interventions in the province of British Columbia (BC). Methods: We performed an observational analysis of the BC Cardiac Arrest Registry (2011–16). We included adults with non-traumatic and EMS-treated OHCA. We examined sex differences in bystander CPR, chest compression rate, and intra-arrest transport using chi-square tests, student's t -test, multivariable linear and logistic regressions. Results: In total, 7398 patients were eligible for the bystander CPR analysis; 31% were female. More males received bystander CPR (54% vs. 50%); however, male sex was not associated with bystander CPR after adjustment for confounders (adjusted OR male vs. female: 1.07, 95% CI 0.96, 1.18). There was no difference in the chest compression rate for males and females in unadjusted or adjusted analyses. Among subjects who did not achieve prehospital ROSC (n = 5225, 32% females), 64% were pronounced dead at the scene with the remaining transported to hospital. Males more often underwent intra-arrest transport than females (36.7% vs. 34.0%). After adjustment, males had 1.2 greater odds of being transported to hospital than females (95% CI 1.04, 1.37). Conclusions: We did not detect an association between sex and bystander CPR or chest compression rate. In those who did not achieve prehospital ROSC, males had 1.2-fold greater odds of being transported to hospital compared to females.